2015
DOI: 10.1515/chilat-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Lactate as a Predictor in Severe Pneumonia

Abstract: SUMMARYFA 25-year-old female's laparoscopy revealed a soft, oval 4 cm lesion in anterior part of uterus between plica vesicouterina and the uterine cervix. Diagnosis of melanoma was made by histological and immunohistochemical method. Inferior median laparotomy with radical hysterectomy type II without ovarectomy was performed. The tumor was staged IVA of the International Federation of Gynecology and Obstetrics classification. The patient was B-RAF mutation negative. Treatment was initiated with chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Likewise, in our study, similar results were obtained with previous publications, and also hemoglobin and hematocrit were lower, especially in patients who did not survive for a month. Furthermore, lactate levels of the non-survivors were signi cantly higher than the survivors, which is reportedly a predictor of severe pneumonia 20 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Likewise, in our study, similar results were obtained with previous publications, and also hemoglobin and hematocrit were lower, especially in patients who did not survive for a month. Furthermore, lactate levels of the non-survivors were signi cantly higher than the survivors, which is reportedly a predictor of severe pneumonia 20 .…”
Section: Discussionmentioning
confidence: 94%
“…In addition to symptoms such as dyspnea, increased LDH, D-dimer, PCT, ferritin, and leukocyte counts, and decreased lymphocyte counts have been speci ed as laboratory parameters that can be used to predict mortality in COVID-19 patients [18][19][20] . Moreover, hemoglobin (HGB) and hematocrit (HCT) values are also critical for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that lactate measurement had clinical utility in initial evaluation and management of pneumonia. [10][11][12][13][14][15][16][17] Several point-of-care devices are available for lactate measurement, which only need microliters of blood. Compared to arterial sampling, capillary sampling is easier to perform, less painful, cheaper, confer faster results, and able to decrease the chance of needle stick injury to health workers.…”
Section: Introductionmentioning
confidence: 99%